1990
DOI: 10.1093/ajcn/52.4.701
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation in elderly nursing home residents increases 25(OH)D but not 1,25(OH)2D

Abstract: Vitamin D metabolism in elderly individuals can be compromised by several mechanisms. We previously described reduced concentrations of 1,25-dihydroxyvitamin D [1,25(OH)2D] in 30% of elderly nursing home residents. The present study assesses the effect of vitamin D supplementation on 25-hydroxyvitamin D [25(OH)D] and 1,25(OH)2D. We performed a double-blind study in which 30 elderly nursing home residents were randomly given either 50 micrograms vitamin D or a placebo daily for 6 wk. Vitamin D metabolites, immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
3
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 26 publications
4
25
3
1
Order By: Relevance
“…In a posthoc analysis, the observed increase in 1,25(OH) 2 (37)(38)(39)(40)(41)(42)(43)(44). Comparisons between those reports and our findings are made difficult by differences in study design that include the ages of the subjects, type and dose of vitamin D administered, duration of vitamin D administration, baseline 25OHD levels, and assays used.…”
Section: Discussioncontrasting
confidence: 47%
“…In a posthoc analysis, the observed increase in 1,25(OH) 2 (37)(38)(39)(40)(41)(42)(43)(44). Comparisons between those reports and our findings are made difficult by differences in study design that include the ages of the subjects, type and dose of vitamin D administered, duration of vitamin D administration, baseline 25OHD levels, and assays used.…”
Section: Discussioncontrasting
confidence: 47%
“…In a recent study performed in osteomalacia, we have also shown that serum OC is a marker of the level of bone turnover, assessed by histomorphometry, and does not correlate with serum la,25(OH)2D (29). Moreover, in the elderly, low doses of vitamin D increase serum 250HD but not la,25(OH)2D3 (19,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 95%
“…Previous research has demonstrated that vitamin D levels have a lag such that changes in behavior should not affect vitamin D levels for at least 6 to 8 weeks. 21,22 When we reanalyzed the data using only patients with samples taken within 2 months of the attack, vitamin D level still had a significant association with attack severity (data not shown).…”
mentioning
confidence: 99%